Targeting bacterial pathogenesis by inhibiting virulence-associated Type III and Type IV secretion systems - Blasey, Nadja; Rehrmann, Daria; Riebisch, Anna Katharina; Mühlen, Sabrina (Frontiers in Cellular and Infection Microbiology, 2023)
Infections caused by Gram-negative pathogens pose a major health burden. Both respiratory and gastrointestinal infections are commonly associated with these pathogens. With the increase in antimicrobial resistance (AMR) over the last decades, bacterial infections may soon become the threat they have been before the discovery of antibiotics. Many Gram-negative pathogens encode virulence-associated Type III and Type IV secretion systems, which they use to inject bacterial effector proteins across bacterial and host cell membranes into the host cell cytosol, where they subvert host cell functions in favor of bacterial replication and survival. These secretion systems are essential for the pathogens to cause disease, and secretion system mutants are commonly avirulent in infection models. Hence, these structures present attractive targets for anti-virulence therapies. Here, we review previously and recently identified inhibitors of virulence-associated bacterial secretions systems and discuss their potential as therapeutics.